PENGARUH KREDIT USAHA RAKYAT TERHADAP PENDAPATAN USAHA TANI CABAI DI KECAMATAN KAKAS BARAT KABUPATEN MINAHASA - lineleyan, gilbert; Rori, George A. P.; Pontoh, Jones (Jurnal Equilibrium, 2023)
In order to determine the influence of initial investment on the revenue of chili producers in Minahasa Regency’s west kakas region, this study attempts to compare the revenues of chili farmers before and after KUR. to determine if the People’s Business Credit affects the income of chili growers in the west kakas region of the Minahasa regency. find out how startup capital and personal business loans affect the income of chili producers in West Kakas Regency. Based on the investigation’s results and the discussion in the chapter before, it was decided as follows: There is a difference in the income of chili farmers before obtaining the People’s Business Credit (KUR) and the income of chili farmers after receiving the People’s Business Credit, according to the results of several paired sample tests carried out using SPSS 22 (KUR) software. The capital variable, which has a positive and considerable effect, contributes to the personal capital’s influence on the income of chili growers in West Kakas Regency. The People’s Business Credit (KUR) obtained has a favorable and considerable influence on the income of chili farmers in the West Kakas District area. Starting capital and People’s Business Credit (KUR), both when considered independently and together, have a beneficial and significant impact on the income of chili farmers in the West Kakas District area. Own capital and, in particular, the People’s Business Credit (KUR) components, have a positive and significant impact.